Detecting deception in children: A meta-analysis - Gongola, Jennifer; Scurich, Nicholas; Quas, Jodi A (Law and human behavior, 2017)
Although research reveals that children as young as 3 can use deception and will take steps to obscure truth, research concerning how well others detect children's deceptive efforts remains unclear. Yet adults regularly assess whether children are telling the truth in a variety of contexts, including at school, in the home, and in legal settings, particularly in investigations of maltreatment. We conducted a meta-analysis to synthesize extant research concerning adults' ability to detect deceptive statements produced by children. We included 45 experiments involving 7,893 adult judges and 1,858 children. Overall, adults could accurately discriminate truths/lies at an average rate of 54%, which is slightly but significantly above chance levels. The average rate at which true statements were correctly classified as honest was higher (63.8%), whereas the rate at which lies were classified as dishonest was not different from chance (47.5%). A small positive correlation emerged between judgment confidence and judgment accuracy. Professionals (e.g., social workers, police officers, teachers) slightly outperformed laypersons (e.g., college undergraduates). Finally, exploratory analyses revealed that the child's age did not significantly affect the rate at which adults could discriminate truths/lies from chance. Future research aimed toward improving lie detection accuracy might focus more on individual differences in children's lie-telling abilities in order to uncover any reliable indicators of deception. (PsycINFO Database Record